Transitions in frailty phenotype states and components over 8 years: evidence from The Irish Longitudinal Study on Ageing - Romero-Ortuno, Roman; Hernndez, Belinda; Kenny, Rose; Knight, Silvin; O'Halloran, Aisling (My University, 2021)
Aim: Fried's frailty phenotype (FP) is defined by exhaustion (EX), unexplained weight loss (WL), weakness (WK), slowness (SL) and low physical activity (LA). Three or more components define the frail state, and one or two the prefrail. We described longitudinal transitions of FP states and components in The Irish Longitudinal Study on Ageing (TILDA). Methods: We included participants aged ≥50 years with FP information at TILDA wave 1 (2010), who were followed-up over four longitudinal waves (2012, 2014, 2016, 2018). Next-wave transition probabilities were estimated with multi-state Markov models. Results: 5683 wave 1 participants were included (2612 men and 3071 women; mean age 63.1 years). Probabilities from non-frail to prefrail, and non-frail to frail were 27% and 2%, respectively. Prefrail had a 32% probability of reversal to non-frail, and a 10% risk of progression to frail. Frail had an 18% probability of reversal to prefrail and 31% risk of death. Probabilities of transitioning from not having to having a component were: 17% for LA, 11% for SL, 9% for EX, 7% for WL and 6% for WK. Probabilities of having a FP component and dying were: 17% for WL, 15% for WK, 14% for SL, 13% for EX, and 10% for LA. Probabilities of having a component and recovering at the next wave were: 59% for WL, 58% for EX, 40% for WK, 35% for LA and 23% for SL. Conclusions: FP states and components are characterized by dynamic longitudinal transitions. Opportunities exist for reducing the probability of adverse transitions.
PUBLISHED
Keywords: Aged; Frailty; Longitudinal; Surveys; Transition; Ageing; Age-related disability; Chronic Health Condition; Third age/ageing